Những câu hỏi liên quan
DH
Xem chi tiết
ND
23 tháng 4 2017 lúc 10:52

1.2.3...2013-1.2.3...2012-1.2.3...20122= (1.2.3...2013-1.2.3...2012) - 1.2.3...20122 = [1.2.3...2012(2013-1)] - 1.2.3...20122 = 1.2.3...2012.2012 - 1.2.3...2012= 1.2.3...20122 - 1.2.3...20122 = 0

Bình luận (0)
DH
Xem chi tiết
NM
Xem chi tiết
NL
6 tháng 1 2015 lúc 19:42

1 . 2 . 3 . ...... 2012 . ( 2013 - 1 - 2012 )

1 . 2 . 3 ..........2012 . (      0     ) = 0 

Bình luận (0)
TL
Xem chi tiết
NN
14 tháng 2 2016 lúc 8:13

b/1.2.3.....2013 - 1.2.3....2012-1.2.3...20122

= (1.2.3...2012.2013-1.2.3...2012)-1.2.3...2012.2012

= 1.2.3...2012(2013-1-2012)

=1.2.3...2012.0=0

Bình luận (0)
LN
9 tháng 2 2019 lúc 10:11

kkkkkkkkkkkkk giải giùm mình đi

 
Bình luận (0)
LN
9 tháng 2 2019 lúc 10:11

nhanh lên nha

 
Bình luận (0)
HM
Xem chi tiết
KT
25 tháng 1 2018 lúc 19:24

a)   \(1.2.3....9-1.2.3...8-1.2.3...7.8^2\)

\(=1.2.3....8.\left(9-1-8\right)\)

\(=1.2.3...8.0\)

\(=0\)

Bình luận (0)
OK
14 tháng 1 2019 lúc 20:17

0 nha

_____________
____________
hok tốt

 

Bình luận (0)
NT
14 tháng 1 2019 lúc 20:22

1 . 1.3 ...9 - 1 . 2. 3...8 - 1.2.3...7.8 mũ 2

= 1.2.3...8. ( 9-1-8)

= 1.2.3...8.0

=0

Bình luận (0)
BN
Xem chi tiết
H24
4 tháng 1 2019 lúc 21:23

                Bài làm

   1.2.3...9 - 1.2.3...8 - 1.2.3...7.82

= 1.2.3...8.( 9 - 1 - 8 )

= 1.2.3...8 .0

= 0

_Chúc_Bạn_Hok_Tốt_^^

Bình luận (0)
OI

\(1.2.3....9-1.2.3...8-1.2.3...7.8^2=1.2.3....8\left(9-1-8\right)=1.2.3....8.0=0\)

Bình luận (0)
DT
4 tháng 1 2019 lúc 21:32

Giải

Ta có: 1.2.3....9 - 1.2.3....8 - 1.2.3....8^2

= 1.2.3....8(9-1-8)

= 1.2.3....8.0

= 0

Bình luận (0)
HK
Xem chi tiết
ZD
27 tháng 1 2016 lúc 14:18

1.2.3.......9-1.2.3...8-1.2.3....82

=1.2.3.......9-1.2.3.........8-1.2.3....8.8

= 1.2.3....8(9-1-8)

=1.2.3......8.0

=0

 

Bình luận (0)
HY
Xem chi tiết
NM
29 tháng 7 2015 lúc 18:57

1234...7x(9-8-1)x82

=0

Bình luận (0)
BL
Xem chi tiết